Effect of concentration of chitosan on the mechanical, morphological and optical properties of tapioca starch film - Ahmad Shapi'i, Ruzanna; Othman, Siti Hajar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Recently, incorporation of natural filler such as chitosan into edible film to produce food packaging material is of particular interest due to the improvement in the properties of the film such as mechanical, morphological and optical properties of the edible film. In this work, tapioca starch-based edible film was prepared with different concentrations of chitosan; 0, 20, 40, 60, 80% w/w of dry starch solid weight. The effects of varying the chitosan concentration on the mechanical properties (tensile strength (TS), elongation at break (EAB), and Young modulus (YM)), morphological and optical properties (color and transparency) of the edible films were investigated. There was 492% increment in TS value of the edible films when chitosan was added up to 60% w/w (21.23 MPa) compared to neat starch film (3.58 MPa). The 60% w/w chitosan films exhibited smooth and even structure which indicated both chitosan and tapioca starch compounds were blended homogeneously. However, 60% w/w chitosan film exhibited very high YM value (2842.5 MPa) and low EAB value (2.46%) which might limit its application. Effects of chitosan concentration on optical properties could be considered negligible. The improvements in TS and morphological structure of the edible films will be beneficial for the potential application of film as food packaging material in which high TS is important to protect the structure of food and while morphological structure can be related to the aesthetical appearance of the food packaging materials.